Emotional self-management in academia - Antoniadou, Marilena; Crowder, Mark (Emerald points., 2021)
Emotional Self-Management in Academiadraws on new empirical research from academics' own personal accounts of emotional experiences from their everyday practice to illustrate how their emotional work is adapting in response to a constantly changing workplace.